1995
DOI: 10.1073/pnas.92.6.2111
|View full text |Cite
|
Sign up to set email alerts
|

A method for probing the topography and interactions of proteins: footprinting of myoglobin.

Abstract: We describe a procedure for mapping residues on the surface of a protein molecule to its sequence, using a scheme that is analogous to nucleic acid footprinting. The protein is end labeled radioactively and subjected to limited proteolysis, and the products are analyzed by denaturing polyacrylamide gel electrophoresis and autoradiography. The method is tested with the heme protein myoglobin and applied to mapping the (unknown) surface of the molecule lacking the heme group: apomyoglobin. Sites of protein-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The use of limited proteolysis to identify binding surfaces has been previously described for several protein interactions (37)(38)(39). In this study, the protease protection analyses provide interesting experimental data on the location of the dimer lateral interface site.…”
Section: Discussionmentioning
confidence: 78%
“…The use of limited proteolysis to identify binding surfaces has been previously described for several protein interactions (37)(38)(39). In this study, the protease protection analyses provide interesting experimental data on the location of the dimer lateral interface site.…”
Section: Discussionmentioning
confidence: 78%
“…The extension of footprinting assays to the study of protein structure was made by Heyduk and Heyduk (1) and Zhong et al (2). These studies showed that, as in the case for nucleic acids, both enzyme and chemical based cleavage reagents are suitable for determining the protected regions within a protein or in a macromolecular complex.…”
mentioning
confidence: 98%
“…A protein footprinting technique has emerged for the study of protein-ligand interactions (Hanai & Wang 1994;Heyduk & Heyduk 1994;Zhong et al 1995), and has been successfully applied to the study of inter-subunit interaction in E. coli RNA polymerase (Greiner et al 1996;Heyduk et al 1996). Protein footprints of a specific complex can be obtained by the nonspecific cleavage of a complex containing the target protein, and visualization of the cleaved fragments containing one or the other terminus after fractionation on SDS-polyacrylamide gels.…”
Section: Introductionmentioning
confidence: 99%